Socialization tactics and person-organization fit - Cable, Daniel M.; Parsons, Charles K. (2001)
We examined how firms' socialization tactics help establish person-organization fit between newcomers and organizations. We used a 3-wave longitudinal design that followed individuals over 2 years: we distributed the first survey before their job search began and the last survey 18 months after their college graduation. Results indicated that newcomers' subjective fit perceptions, as well as changes in their values, were associated with two types of socialization tactics: content (i.e., tactics that are sequential and fixed vs. variable and random) and social aspects (i.e., tactics and emphasize serial and investiture processes rather than disjunctive and divestiture processes). The context dimension of socialization tactics, where socialization is collective and formal (vs. individualized and informal), was not related to P-O fit in this study. - Reproduced
Keywords: Organizations; Personnel management